2014
DOI: 10.12691/jfnr-2-12-26
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Unsaponifiable Fraction from Palm Fatty Acid Distillate on Lipid Profile of Hypercholesterolaemia Rats

Abstract: Physical refining of palm oil by deodorization produces palm fatty acid distillate (PFAD) that contains some bioactive compounds such as vitamin E (tocopherol and tocotrienols), phytosterol, and squalene. These bioactive compounds were accumulated in unsaponifiable fraction. This study aimed to use USF as a source of bioactive compounds for lowering cholesterol that tested in vivo by using hypercholesterolaemia rats. The rats were divided into 4 groups that administered by USF of 0, 200, 500, 1000 mg/kg bw/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
2
1
0
2
Order By: Relevance
“…The unsaponifiable matter value was 2.78%, which is in the range described by Top [ 42 ] (1.5%–3.4%). The vitamin E content of the PFAD used in this study was 0.19%, which is in agreement with the vitamin E content reported by Estiasih et al [ 43 ] (0.1956%).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The unsaponifiable matter value was 2.78%, which is in the range described by Top [ 42 ] (1.5%–3.4%). The vitamin E content of the PFAD used in this study was 0.19%, which is in agreement with the vitamin E content reported by Estiasih et al [ 43 ] (0.1956%).…”
Section: Resultssupporting
confidence: 92%
“…Additionally, the crystallization temperature of 34.7 C (Figure 1) is associated with the formation of fat crystals as reported by Ngoc Doan et al [15] The unsaponifiable matter value was 2.78%, which is in the range described by Top [42] (1.5%-3.4%). The vitamin E content of the PFAD used in this study was 0.19%, which is in agreement with the vitamin E content reported by Estiasih et al [43] (0.1956%).…”
Section: Quality Parameters Valuesupporting
confidence: 93%
“…The bioactive compounds from USM such as polyphenols, phytosterols, tocopherols, and vitamins (soluble in fat) have a potential effect as antioxidants and antimicrobials (Mohamed et al, 2018). Estiasih et al (2014) reported that USM of palm fatty acid distillate decreased total cholesterol, LDL cholesterol, and triglyceride and increased HDL cholesterol level in hypercholesterolemic rats. The unsaponifiable matter content of peanut oil samples ranged from 0.98 to 1.52%.…”
Section: Unsaponifiable Matter (Usm)mentioning
confidence: 97%
“…Salah satu dampak negatif dari meningkatnya perjudian slot online adalah meningkatnya kasus kecanduan judi di masyarakat (Kementerian Kesehatan Republik Indonesia, 2018). Menurut penelitian (Estiasih et al, 2014) prevalensi gangguan perjudian di Indonesia mencapai 3,8 persen dari populasi orang dewasa. Kecanduan perjudian online ini dapat merusak kohesi keluarga karena dapat menyebabkan perilaku kompulsif, toleransi, impulsif, dan masalah keuangan pada kepala keluarga (Griffiths 2005;Kuss & Griffiths 2012;Kim et al2016dalam (Asran Abdullah, La Parasit, 2019).…”
Section: Pendahuluanunclassified